Quantum Dielectric Model for Energy Loss of Particles in Astrophysical Plasmas - Archubi, Claudio Darío (2023)
We present the results obtained using a novel quantum approach to describe the interaction of charged particles with the astrophysical type of plasmas, based on the dielectric plasma-wave-packet model (PWPM) together with a full description of statistical effects on energy exchange processes. We use this formulation to calculate the energy loss moments for protons, positrons, and electrons traversing different stellar plasmas on a wide range of projectile velocities and plasma densities and temperatures. We consider special quantum restrictions for the cases of positrons and electrons, including relativistic corrections for high-velocity particles. We analyze and compare the results for different cases of main interest, from dilute solar-corona plasma to cases of increasing densities in the interior of the sun and in the dense regions of giant stars.